2021
DOI: 10.2196/26176
|View full text |Cite
|
Sign up to set email alerts
|

Seeking Help From Trusted Adults in Response to Peers’ Social Media Posts About Mental Health Struggles: Qualitative Interview Study Among Latinx Adolescents

Abstract: Background Rather than confiding in adults about their mental health struggles, adolescents may use social media to disclose them to peers. Disclosure recipients are tasked with deciding whether to alert an adult and, if so, whom to alert. Few studies have examined how adolescents decide on a trusted adult to help a friend who posts on social media about his/her mental health struggles. Moreover, Latinx adolescents are underrepresented in research on social media use, which creates gaps in understa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
3
1
Order By: Relevance
“…But we also recognize that our sample is not representative. Minorities are underrepresented in research on adolescent use of social media and mental health, the unique experiences and context of minority adolescence may diverge from our findings (Campos-Castillo et al, 2021). It may also be that the implications of disconnection are more severe for rural youth.…”
Section: Discussioncontrasting
confidence: 63%
“…But we also recognize that our sample is not representative. Minorities are underrepresented in research on adolescent use of social media and mental health, the unique experiences and context of minority adolescence may diverge from our findings (Campos-Castillo et al, 2021). It may also be that the implications of disconnection are more severe for rural youth.…”
Section: Discussioncontrasting
confidence: 63%
“…Caregivers are critical in suicide prevention, especially for Latino adolescents in the United States (Boyas et al, 2019; Campos-Castillo et al, 2021; Gulbas & Zayas, 2015; O’Gara et al, 2022). However, few suicide prevention efforts target Latino caregivers, and even fewer consider their needs and preferences when developing those programs (Leong & Leach, 2010; Villarreal-Otálora et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Campos-Castillo et al (2021) found that Latinx adolescents sought out mental health support from trusted adults with experiential knowledge, authority, and close emotional and physical proximity to the adolescents. Their findings also showed that having immigrant parents influenced the type of support the adolescents sought out due to unique barriers, making it imperative that Latinx adolescents receive the proper type of instrumental and emotional support from trusted adults that are not their parents (Campos-Castillo et al, 2021). In this study, the Latina participants may have had trusted adults who did not provide the resources and support they needed to protect against peer victimization.…”
Section: Discussionmentioning
confidence: 99%
“…Another consideration that may have influenced this association is the nature of the relationship between Latina adolescents and their trusted adults. Campos-Castillo et al (2021) found that Latinx adolescents sought out mental health support from trusted adults with experiential knowledge, authority, and close emotional and physical proximity to the adolescents. Their findings also showed that having immigrant parents influenced the type of support the adolescents sought out due to unique barriers, making it imperative that Latinx adolescents receive the proper type of instrumental and emotional support from trusted adults that are not their parents (Campos-Castillo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%